On the causes and consequences of deviations from rational behavior - Dainis Zegners; Uwe Sunde; Anthony Strittmatter (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2020)
This paper presents novel evidence for the prevalence of deviations from rational behavior in human decision making - and for the corresponding causes and consequences. The analysis is based on move-by-move data from chess tournaments and an identification strategy that compares behavior of professional chess players to a rational behavioral benchmark that is constructed using modern chess engines. The evidence documents the existence of several distinct dimensions in which human players deviate from a rational benchmark. In particular, the results show deviations related to loss aversion, time pressure, fatigue, and cognitive limitations. The results also demonstrate that deviations do not necessarily lead to worse performance. Consistent with an important influence of intuition and experience, faster decisions are associated with more frequent deviations from the rational benchmark, yet they are also associated with better performance.
Keywords: D01; D9; C7; C8; 330; Rational strategies; Artificial Intelligence; Behavioral Bias